Work life balance and work engagement on employee performance in the auto cutting department - Fauzi, Haris (Indonesian Journal of Multidisciplinary Science, 2024)
The business world's explosive expansion and development have given rise to new industries and commercial prospects. Human resources in the company are said to be the main ones because human resources themselves determine the direction and goals of the company. Considering the critical role that human resources play, it makes sense for a business to retain its human capital by closely monitoring employee performance. The outcome of an individual's job, in relation to both number and quality, is their performance as an worker executing their assigned tasks in conformity with their responsibilities. This study aims to investigate the connection between employee engagement and work-life balance have on productivity in the PT. Shoetown Ligung Indonesia Auto Cutting Department. The researchers' analytical approach makes use of a descriptive verification method. With a sample size of 124, the study's population consisted of 225 workers from PT. Shoetown Ligung Indonesia's auto cutting department. Probability sampling combined with basic random sampling is the sample method utilised. To gather information for this research, Likert scale questionnaires were distributed. The multiple regression analysis, or the traditional assumption test, simultaneous analysis of the determination coefficient, and partial determination coefficient analysis are the analysis techniques that are employed. The study's findings show that employee performance and work-life balance are positively and dramatically impacted by engagement, partially and simultaneously. The study's conclusions can be used as a foundation for enhancing and preserving employee performance, work-life balance, and engagement at work.